Synthetic biology, security and governance - Lentzos, Filippa (Biosocieties, 2012)
The twenty-first century has witnessed an increasing confluence of rapidly advancing science and its embodiment in practical technologies, an extensive global diffusion of the knowledge and capabilities associated with those developments, and a seemingly unending shift in the international security environment. The scope and intensity of these interactions in the life sciences have generated concern about security risks stemming from possible misuse. This lecture focuses on one of the key emerging life science technologies of concern, gene synthesis, and considers how the new risks and challenges it poses for governance can best be managed.